INFLUENCE OF VARIETIES AND FERTILIZATION ON GROWTH AND YIELD OF SWEET SORGHUM GROWN AS MAIN AND RATOON CROPS - M. GANGA DEVI (The Journal of Research ANGRAU, 2016)
A field experiment was conducted at S.V. Agricultural College, Tirupati of Acharya N.G. Ranga Agricultural University during kharif and rabi seasons of 2010 and 2011. The experiment was laid out in a split-split plot design and replicated thrice. The results revealed that all the growth parameters viz., plant height, leaf area and dry matterproduction and yield parametres stalk yield and grain yield of sweet sorghum grown as main crop were recorded highest with variety SPV-422 followed by Madhura hybrid with application of 100-80-80 kg ha-1 N, P2 O5 and K2 O. The ratoon crop of sweet sorghum also followed same trend and recorded highest yield with application of 125 per cent of the nitrogen applied to main crop than the other treatments tested in this study.